PENGARUH ATMOSFER KAFE, DAYA TARIK PROMOSI, DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING (Studi Pada Kafe Blackbone Coffee Banyumanik, Semarang) - Lestari, Yessi; Soesanto, Harry (Diponegoro Journal of Management, 2017)
Food business is one of the favorite business in Semarang, especially café. It’s proven with the rising of the growth number by 2010 to 2016 in Semarang area. One of the favorite café is Blackbone Coffee, located in Banyumanik. The tight competition in this business become one of the factor of decreasing selling in Blackbone Coffee. Therefore creative ideas are needed to hold the business on.The  goal  of  this  study  is  to  explain  the  influence  of  the  café’s  atmosphere, promotion appeal, and product’s variety to the purchase decision, where the brand image is used as the intervening variable between the café’s atmosphere, promotion appeal, and product’s variety of the purchase decision in the Blackbone café. Those factors have the biggest impact in the purchase decision by the customers. Sample were collected from 100 respondents. Respondents' answers were analyzed by Multiple Linear Regression using SPSS program.The result show that café’s atmosphere, promotion appeal, and product variety has positive and significant impact on brand image variable. 0,383 for café atmosphere, 0,161 for promotion appeal, and 0,459 for product variety. Brand image as the intervening variable has positive and significant impact on purchase decision variable with 0,443.